Swa-Anguli Pramana of Shira (Head) in Asthi-Sara-Purusha (Person Having Enriched Bone Tissue) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda is an ancient Indian holistic medicine system focusing on promoting health by maintaining body balance. It is gaining relevance in today's integrative medicine landscape for treating chronic diseases. Key Ayurvedic concepts like Shira Pradesha, Maha Shira, and Asthi-Sara-Purusha contribute to individual health assessment. Methods: This review examines the applicability of Ayurvedic anthropometric methods, particularly Swa-Anguli Pramana, in current clinical practice. It includes discussions on validation studies and comparative analyses with modern techniques. Results: Swa-Anguli Pramana shows consistent personalized diagnostic potential across different demographic groups. Challenges exist regarding discrepancies with modern measurements and the need for standardization. Discussion: Integrating Ayurvedic measurements with modern metrics is likely to be valid and acceptable in contemporary healthcare. There is growing interest in traditional measurement methods for providing personal health information aligned with the holistic approach of Ayurveda. Conclusion: Ayurvedic anthropometric methods, especially Swa-Anguli Pramana, have potential for individualized health assessment. Standardization and validation are vital, and future research should focus on establishing a standardized integrative framework.